Answer:
(4,8)
Step-by-step explanation:
4 + 8 = 12
3(4) + 8(8)
= 12 + 64
= 76
Answer:
12
Step-by-step explanation:
you first make an equation of 5/6x = 10, then divide 5/6 on both sides to get x = 12
This answer is going to be X=-5 because you are solving for X in the parentheses.
The Answer would be p(m)=25+10 because she started with a base pay of 10 dollars and the next lawn she charge 35 meaning it makes the rate of change 25
Answer:
C. 0, -1, 3
Step-by-step explanation:
Note: There is no graph. I assume you mean "zeroes/roots" by "solutions".
x(x^2-2x-3)=0
/(x^2-2x-3)
x=0
x^2-2x-3 = x^2+x-3x-3 = x(x+1) + ( -3(x+1) = (x-3)(x+1)
/(x-3) --> x +1 =0, x=-1
/(x+1) --> x-3 = 0, x=3